Relationship between heat input and microstructure and mechanical properties of laser beam welded superalloy inconel 718 - Odabaşi, Akin; Ünlü, Necip; Göller, Gültekin; Eruslu, M. Niyazi; Kayali, E. Sabri (Minerals, Metals and Materials Society, 2012)
Autogenous butt, laser beam welds were carried out using Inconel 718 alloy sheets (2.1 mm thick). The relationship between heat input laser beam welding (LBW) and the microstructural and mechanical properties of superalloy Inconel 718 were investigated. Nine different heat inputs in the range of 61.29-90.09 Jmm-1 were applied to evaluate the geometry of weld seams. Full penetration was achieved in all weld experiments. Optical and field emission scanning electron microscopy and microhardness tests were performed. Test results indicate that increasing the amount of heat input from 61.29 Jmm -1 to 90.09 Jmm-1 presented solidification rates between 1.27×105 and 1.46×106°Cs-1. The hardness property of the weld samples decreased with the increasing the heat input.
141st Annual Meeting and Exhibition, TMS 2012 -- 11 March 2012 through 15 March 2012 -- Orlando, FL -- 89569
Keywords: Hardness; Inconel 718; Laser welding; Solidification rate